2004
DOI: 10.1002/rcs.3
|View full text |Cite
|
Sign up to set email alerts
|

Human tactile perception as a standard for artificial tactile sensing—a review

Abstract: In this paper, we examine the most important features of human skin tactile properties with special emphasis on the characteristics which are vital in the design of artificial systems. Contrary to the visual and auditory senses, the touch signal is not a well-defined quantity. As a result, the researchers of this field are still dealing with the basics of collecting the most relevant data. Following this, mimicking the sense of touch by producing artificial tactile skin is a challenging process. Although the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
159
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(162 citation statements)
references
References 30 publications
3
159
0
Order By: Relevance
“…[6][7][8] in the considered frequency range, in accordance with the literature [16]. As before, the measurements are not influenced by long-time relaxations.…”
Section: Piezoelectric Modulisupporting
confidence: 86%
See 1 more Smart Citation
“…[6][7][8] in the considered frequency range, in accordance with the literature [16]. As before, the measurements are not influenced by long-time relaxations.…”
Section: Piezoelectric Modulisupporting
confidence: 86%
“…Used as isolated sensors/actuators or assembled into more complex multimodal devices, they offer challenging solutions in many application fields including robotics. For these reasons they can be regarded as interesting candidates for tactile sensors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the social implications of this medium is critical to media psychology. Touch is a distinctive interaction mode of robots afforded by their physical presence (Dargahi & Najarian, 2004;Li, 2015). Natural physical contact between people and "personal service robots" (International Federation of Robotics, 2005) could be beneficial, yet it is unclear how physiological effects of interpersonal touch apply to social robots.…”
Section: Introductionmentioning
confidence: 99%
“…There are various QST methods, such as a simple patient answer of yes or no whether stimuli could be identified [24], choice between one out of two time periods that include stimuli [25], or when the patient is asked to press a button when a vibration stimuli is perceived and to press again when the stimulus disappears (the method of limits) [26]. Sensibility studies using vibration as stimuli have shown that mechanoreceptors in the skin can detect vibration frequencies between 0.4 and 800 Hz [27]. However, most published clinical data are from studies on patients with various type of neuropathic conditions [28][29], and in those studies, vibration frequencies between 20 and 250 Hz have been used as stimuli [28][29][30].…”
Section: Introductionmentioning
confidence: 99%